Clinical Characteristic and Severity of Molar-Incisor Hypomineralisation in 8-10 Years Old - Enrita Dian Rahmadini; Arianne Dwimega; Maria Aninggadita Priskawati (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2025)
Background: Molar Incisor Hypomineralization (MIH) is a qualitative developmental defect of tooth enamel that affects one or more permanent first molars and may involve incisors. The clinical features of MIH can include demarcated opacities, post-eruptive enamel breakdown, atypical caries, atypical restorations, and missing teeth due to MIH. Molar incisor hypomineralization is a common enamel defect with a relatively high prevalence worldwide, ranging from 9.2% to 14.2%. Data on the prevalence of MIH and clinical features of MIH in Indonesia are still minimal. Objective: To observe the distribution of clinical features and severity of molar-incisor hypomineralization in children aged 8-10 years in Kemanggisan urban village. Materials and Methods: This study used a descriptive observational study with a cross-sectional method. Data was collected through random sampling by examining 267 child subjects in the field. Results: The prevalence of MIH in Kemanggisan urban village was 29,2%. There was no significant difference in gender and age in the distribution of clinical features and severity levels. The highest prevalence of clinical features and severity levels were demarcated opacities and mild, at 9,6%. Conclusion: The most prevalent clinical feature and severity level was demarcated opacities and mild in children aged 8-10 years in Kemanggisan urban village.